Variable cross-correlation code construction for spectral amplitude coding optical CDMA networks - Hilal Adnan, Fadhil, Dr.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hassan Y., Ahmed; Hamza Mohammed Ridha, Al-Khafaji (Elsevier Ltd., 2012)
Link to publisher's homepage at http://www.elsevier.com/